MICROPROPAGATION AND GENETIC TRANSFORMATION OF TION OF BANANA ( BANANA (Musa paradisiaca Musa paradisiaca L. cv. Chinia) . Chinia - TRIBHUWAN KUMAR; RAVI SHANKAR SINGH; RAVI KESARI; AWADHESH KUMAR PAL (The Bioscan, 2018)
An attempt was made to develop callus mediated regeneration system and to check response towards Agrobacterium mediated transformation in the local variety of Banana (Musa paradisiaca L. cv. Chinia) cultivar Chinia. Callus induction was observed when male flower aggregates of 1 cm was used as explants and cultured in the MS media added with 2.5 mg/L 2, 4 D, 0.5 mg/L IAA, BAP 1mg/L and 0.5 gm/L of charcoal under dark condition at 25º C. MS medium fortified with 1.0 mg/l BAP with a fixed concentration of NAA (0.2 mg/l) and glutamine (100 mg/ l) or with a fixed concentration of IAA (0.5 mg/l) and Caesin hydrolysate (500 mg/l), under 1500 lux intensity with 16/8 h light/dark cycle resulted in significant shooting. The combination of 1 mg/l of IBA and 2mg/l of NAA among three (0.5, 1.0 and 2.0 mg/l each) different concentration of two auxins viz., IBA and NAA in MS media resulted in distinct rooting. This local variety also showed response towards Agrobacterium mediated transformation with regeneration efficiency 1-2% when examined through GUS expression assay. The developed regeneration system and response towards Agrobacterium mediated response hold much scope for the genetic improvement and wide multiplication of this local cultivar of banana.